2022
DOI: 10.1021/acs.orglett.2c03084
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Organoboron/Palladium Catalysis for Regioselective N-Allylations of Azoles with Allylic Alcohols

Abstract: A method for regioselective palladium-catalyzed allylic alkylation of ambident nitrogen heterocycles, employing simple allylic alcohols as electrophile precursors, is described. An organoboron co-catalyst serves both to activate the azole-type nucleophile toward selective N-functionalization and to accelerate the formation of a π-allylpalladium complex from the allylic alcohol. The method can be applied to various heterocycle types, including 1,2,3-and 1,2,4-triazoles, tetrazoles, pyrazoles, and purines, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Recent research from our group has shown that arylboronic acid or diarylboronic acid catalysts can be used to achieve regioselective N -functionalizations of azoles with a variety of partners, including epoxides, α,β-unsaturated carbonyl compounds, and allylic alcohols (Scheme ). , In each case, it was proposed that the organoboron catalyst activated both the azole nucleophile (via B–N coordination) and the electrophile. Considering that the method enabled functionalizations of purine derivatives, along with other azole nucleophiles that could serve as nucleobase analogues, we aimed to develop an N -glycosylation method based on this activation mode.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research from our group has shown that arylboronic acid or diarylboronic acid catalysts can be used to achieve regioselective N -functionalizations of azoles with a variety of partners, including epoxides, α,β-unsaturated carbonyl compounds, and allylic alcohols (Scheme ). , In each case, it was proposed that the organoboron catalyst activated both the azole nucleophile (via B–N coordination) and the electrophile. Considering that the method enabled functionalizations of purine derivatives, along with other azole nucleophiles that could serve as nucleobase analogues, we aimed to develop an N -glycosylation method based on this activation mode.…”
Section: Introductionmentioning
confidence: 99%
“…By employing allylic alcohols as the electrophiles in the presence of a palladium bis­(phosphine) cocatalyst, regioselective dehydrative N-allylations of various azoles were achieved (Scheme ). Control experiments showed that the organoboron catalyst has a significant effect on both reaction rate and N-allylation regioselectivity, suggesting that it plays a role both in activating the allylic alcohol electrophile, in cooperation with the Xantphos­(Pd) complex, and the azole nucleophile. , The allylation method has been extended to other NH-pronucleophiles, including pyridones and sulfoximines …”
Section: Introductionmentioning
confidence: 99%
“… 1 Due to the industrial significance of this heterocycle class, substantial efforts were invested into method development and strategical concepts for their bespoke and diversified syntheses. 2 In this context, 3 electrophilic allylations of azoles were shown to offer an expedited avenue toward valorized building blocks and synthetic intermediates for established pharmaceuticals, drug leads, and agrochemicals. 4 The direct redox-coupling of 1,2-di- or higher substituted alkenes to azoles without any prefunctionalization 5 of either reactant provides a streamlined, highly redox economic 6 avenue to customized target structures.…”
Section: Introductionmentioning
confidence: 99%